Effect of valve opening optimization on fuel delivery and combustion efficiency in a multi-burner waste-oil heating system - Burhan Hafid; Erwen Martianis; Murdani; Siti Umira; Abdul Gafur (JTTM : Jurnal Terapan Teknik Mesin, 2026)
The utilization of waste oil as an alternative fuel has considerable potential for small-scale heating and distillation systems; however, its combustion performance is strongly influenced by fuel flow regulation and burner configuration. Most previous studies have primarily investigated single-burner waste-oil systems, resulting in limited understanding of valve opening effects in multi-burner configurations commonly used in practical applications. This study experimentally evaluates the effect of valve opening angle on fuel delivery and combustion performance in a three-burner waste-oil stove using SAE 10W-40 waste oil. Valve openings of 30°, 35°, and 40° were tested, with all burners operating simultaneously under the same airflow conditions. Combustion performance was evaluated based on fuel consumption, combustion temperature, heat release, and thermal efficiency. Experiments were conducted under steady-state conditions with a fixed combustion duration; fuel consumption was measured volumetrically and flame temperature was recorded using K-type thermocouples, with each test repeated three times to improve data reliability. At a 40° valve opening, the fuel flow rate of 448–488 mL/min represents variations among individual burners operating concurrently, while the combustion temperature range of 633–679°C reflects the experimental spread measured across the three burners. The results show that increasing valve opening increases fuel flow and heat release; however, excessive valve opening leads to an imbalance between fuel supply and available air. At a 35° opening, the fuel flow rate is sufficiently high while still allowing adequate air entrainment, producing a more favorable air–fuel mixing condition compared to lower and higher openings. In contrast, the 40° opening causes over-fueling, resulting in unstable flames, soot formation, and incomplete combustion despite higher energy input. These conditions are directly associated with reduced operational safety due to flame instability and increased soot deposition.The main contribution of this study is providing experimental evidence on valve opening optimization in a multi-burner waste-oil combustion system, offering practical guidance for improving efficiency, combustion stability, and safe operation in waste-oil-based heating applications.